2018
DOI: 10.1089/end.2018.0459
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience with Narcotic-Free Ureteroscopy: A Feasibility Analysis

Abstract: Attempts to reduce the number of narcotic prescriptions are paramount in the fight against narcotic addiction in the United States. Although our initial cohort is small, this feasibility study provides compelling evidence that nf-URS is a safe and effective practice. Furthermore, nf-URS resulted in a dramatic decrease in the number of narcotics circulating in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Recent studies have demonstrated success in opioid‐free postoperative pain control. A retrospective review of patients undergoing cystoscopy found that prescribing patients diclofenac instead of hydrocodone or oxycodone resulted in nearly identical number of calls for postoperative pain issues . Non‐narcotic management of postoperative pain following pediatric robotic pyeloplasty showed shorter length of stay without increase in complications .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated success in opioid‐free postoperative pain control. A retrospective review of patients undergoing cystoscopy found that prescribing patients diclofenac instead of hydrocodone or oxycodone resulted in nearly identical number of calls for postoperative pain issues . Non‐narcotic management of postoperative pain following pediatric robotic pyeloplasty showed shorter length of stay without increase in complications .…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Opiate-free protocols after ureteroscopy have been shown to be feasible. 23 Intraoperative use of nonopiate medications, such as intravenous toradol and belladonna opium suppositories have been shown to help with postoperative pain control after ureteroscopy. 11,24 Notably in this study, no surgical factors were identified as risk factors for persistent opiate use, including stent duration or sheath use.…”
Section: Discussionmentioning
confidence: 99%
“…1 F-URS is increasing in prevalence, 16 and with new frontiers in opioid-free surgery and cost containment. 17,18 A significant amount of resources are directed toward sterile processing, 19 maintaining, repairing and replacing flexible endoscopes. 20 In the last 5 years, numerous publications have evaluated the safety, quality, environmental impact and cost of disposable ureteroscopes.…”
Section: Discussionmentioning
confidence: 99%